ANALYSIS OF THE CONSTITUTIONAL AND LEGAL FOUNDATIONS OF RELATIONS IN THE FIELD OF CULTURAL HERITAGE - Ahmedov , Axadulla (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
This article examines the function and significance of the Republic of Uzbekistan’s Constitution, the country’s foundational law, in the protection of cultural assets. It provides information on the legal status of the cultural heritage sector, its pressing issues, the formation stages of organizations authorized to manage this field, and the main regulatory legal documents governing cultural heritage relations. The article also presents a comparative analysis of how the concepts of culture, science, education, monuments, and national heritage are reflected in the Constitutions of Uzbekistan and certain foreign countries, as well as the legal norms related to the cultural heritage sphere. Moreover, the author of the article outlines current legislative problems and shortcomings, offering proposals regarding the necessity of adopting a “Cultural Heritage Code.”